1993
DOI: 10.1210/jcem.76.3.8095269
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and efficacy of a long-acting formulation of the new somatostatin analog BIM 23014 in patients with acromegaly.

Abstract: The treatment of acromegalics with somatostatin analogs requires continuous sc infusion using pumps or several sc injections daily. Long-acting formulations (BIM-LA) of BIM 23014 (BIM) using delayed microcapsules may provide a more convenient form of therapy. Fourteen acromegalics whose GH secretion had not been normalized by transphenoidal surgery followed, in 10 cases, by pituitary radiotherapy (performed at least 2 yr before the study) were studied. Eight of these patients participated in an initial study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 29 publications
7
42
0
1
Order By: Relevance
“…In agreement with other trials with lanreotide SR (16,22,25), we observed a small rise in fasting blood glucose during therapy, whereas others found no change in glucose metabolism (23). In our study, as well as in others (22,23), no obvious deterioration in glucose metabolism was seen in patients with overt diabetes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with other trials with lanreotide SR (16,22,25), we observed a small rise in fasting blood glucose during therapy, whereas others found no change in glucose metabolism (23). In our study, as well as in others (22,23), no obvious deterioration in glucose metabolism was seen in patients with overt diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…By contrast, only 2 of 11 patients (18%) reached a normal IGF-I when the interval was further reduced from 10 to 7 days. This can be explained by the speci®c pharmacological pro®le of the drug reaching a maximum effect after 9 days: a mean IGF-I suppression of 80% at day 4, 83% at day 9 versus 53% at day 14 was obtained (16). This pro®le also explains why a further reduction of the dose interval from 10 to 7 days is less bene®cial.…”
Section: Discussionmentioning
confidence: 99%
“…A long-acting intramuscular formulation of lanreotide also controls growth hormone secretion in patients with acromegaly, but its duration of action is two weeks at most. 73 …”
Section: New Forms Of Somatostatin Analoguesmentioning
confidence: 99%
“…Octreotide can control GH and insulin-like growth factor (IGF-1) secretion, on average, in approximately two-thirds of patients with acromegaly and, when used as primary therapy, it can induce significant tumour shrinkage in approximately 30% of patients (4,5). Lanreotide, an alternative SA of comparable potency, is available as twice-weekly or monthly preparations (4,6,7).…”
Section: Introductionmentioning
confidence: 99%